Kazem Jawad is a poet - kareem, Ahmed Hameed (Al-Adab Journal, 2015)
Through my study of modern Iraqi poetry and found that there are poets who did not get luck of the study and care researchers have Ogvlhm did not shed light on their livesor on the literary Ntegathm despite being poets who employed their poems to sing the glories of their homeland and nation and treated in their hair many humanitarian issueswith possessing literary talents for a less than their peers in both the quality of the purposes for which they were Atrkonha or stages of development to keep pace withinnovation in Arabic literature. Among those poets Kazim Jawad He has never been an independent knowingly reportedly only about his hair from premature monetary signalsin point of time, his hair remained trapped Mnzhoya on the shelves waiting for him toshake the dust. Therefore determined to study his life and his poetry came to this research titled (Kadhim Jawad, a poet). Has been adopted in these studies on the divan poet marked (from Songs of freedom)which is the only court which issued the poet in 1960 also adopted along with Diwanother poems set published in newspapers, magazines and unpublished poemsannexed sincere Azmi marked the book (Kadhim Jawad life and its effects). The research methodology was the approach technically analytical, also divided thesearch on the front of the boot and the two sections followed proved in sources and references dealt with in the boot poet's life from his birth until his death, and the first topic dealt with it Kadhim Jawad environment poetry and his views on poetry and literature and influenced by some contemporary poets him and poetic themes, represented by the national direction and the direction of national and humanitariandirection. The second section devoted to the study of a language Jawad Kadhim poetry includinginfluenced by the language of the Koran, and the language of the literary heritage as well as contemporary poets influenced by the language and the language of the political dictionary Moreover, syntax and vocabulary systems. I've highlighted this search light on the life of poet immersed hired his personal life and literary in his homeland issues of service and the nation, came poems Cilgelh, Vahzmotivation and instigated the revolution and called for the advancement of the state oflethargic who wear the nation in his time, this as well as his call to address the manyhumanitarian issues, dealt with all poems expressive and clear images derived fromreality. And last but not least, I hope God Almighty Aziz that I have been able to add a newbrick to the edifice of Arab literature in Arabic and the library, and the help of God andreconcile. Researcher